Racial and Ethnic Disparities in Cardiotoxicity in Patients With Cancer Treated With Anthracyclines - Lili Zhang; Justin Song; Waqas Hanif; Rachel Clark; Magued Haroun; Caroline McNaughton; Leandro Slipczuk; Mario J. Garcia; Min Pu; Carlos A. Gongora; Tomas G. Neilan; Della Makower; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Cardiotoxicity in patients with cancer treated with anthracyclines is associated with increased morbidity and mortality. We aimed to examine the incidence of and risk factors for cardiotoxicity in a racially and ethnically diverse cohort with cancer treated with anthracyclines. Methods We included consecutive adult patients who underwent anthracycline‐based chemotherapy from 2016 to 2019 for any type of cancer. The end point was the development of cardiotoxicity (defined as clinical heart failure or drop in left ventricular ejection fraction ≥10% to ≤50%). Results A total of 743 individuals were included (28.0% Non‐Hispanic [NH] White, 30.5% NH Black, 38.5% Hispanic, 3.0% Asian). Hypertension, diabetes, hyperlipidemia, obesity, and low socioeconomic status were more common in NH Black and Hispanic individuals. During a median follow‐up of 21 months, 98 individuals (13.2%) developed cardiotoxicity. The incidence of cardiotoxicity was significantly higher in NH Black (16.3%), Hispanic (14.7%) and Asian (18.2%) individuals than in NH White (7.2%) individuals (P=0.024). After adjusting for cardiovascular risk factors, socioeconomic status score, anthracycline dose, baseline left ventricular ejection fraction, and cancer type, being NH Black (hazard ratio [HR], 2.62 [95% CI, 1.23–5.56]) or Hispanic (HR, 2.37 [95% CI, 1.11–5.07]) was independently associated with a higher risk of cardiotoxicity. NH Black and Hispanic individuals had a greater decline in left ventricular ejection fraction compared with NH White and Asian counterparts. The associations between baseline characteristics and incident cardiotoxicity were similar across different racial and ethnic groups. Conclusions In a large retrospective multiracial and ethnic cohort treated with anthracyclines, NH Black, Hispanic, and Asian individuals had an increased risk of cardiotoxicity compared with their NH White counterparts.